Auditing on usage of statistical sampling in the traditional and electronic systems and their impact on Auditing risks - د / صديق سبيل آدم منصور (White Nile Journal for Studies and Research, 2026)
This research tackles the audit on usage of statistical sampling and its impact on audit risks in the traditional and electronic system The research's problem focuses on That nowadays institutions and firms have been expanded. therefore accounting transactions have been widened and became so huge in its size, although the time allowed for completing the audit programme is limited, hence accordingly numerous errors have been detected and that created many risks which have been risen also according to that size The research followed the descriptive, historical, conductive and deductive methods to collect data and prepare the hypotheses and to make schedules. The research targeted on the following results when we perform extra quality of internal audit and internal check that will reduce audit risks when applying statistical sampling Hence external auditors prefer performing full audit than the statistical sampling audit The research has conducted the following recommendations to rely on internal check procedures besides the usage of statistical sampling in auditing the big institutions and firms according to the electronic system used, besides performing internal audit to access the important accounting activities in the big institutions and firms The conclusions arrived at have accepted the three hypotheses. Finally the study is conducted with recommendations relevant to the findings of the study in general.